Design and Simulation of a Compact UWB MIMO Antenna with Mutual Coupling Reduction - Narges Malekpoor (Journal of Intelligent Procedures in Electrical Technology, 2016)
In this paper, A compact multiple-input-multiple-output (MIMO) antenna with a small size of 26×31mm2 is proposed for portable ultrawideband (UWB) applications. The antenna consists of two square-monopole antenna with microstrip-fed by a 50- Ω printed on one side of the substrate. To enhance isolation and increase impedance bandwidth, two long ground stubs are added to the ground plane on the other side. Simulation is used to study the antenna performance in terms of reflection coefficients at the two input ports, coupling between the two input ports, radiation pattern, realized peak gain, efficiency and envelope correlation coefficient. Results show that the MIMO antenna has an impedance bandwidth ( for S22< -10 dB) of larger than 3.1–10.6 GHz, low mutual coupling ( for S21< 3 dB) of less than -16 dB, and a low envelope correlation coefficient of less than 0.003 across the frequency band, making it a good candidate for portable UWB applications.